Representations Can be Good Enough - O'Neill, Jacki; Castellani, Stefania; Grasso, Antonietta; Roulland, Frederic; Tolmie, Peter (Springer, 2005)
When working remotely with physical objects obvious problems of reference arise because of the lack of a mutually shared object. Systems aiming to support such work tend to be based on understandings of face-to-face interaction and frequently use video. However, video introduces new interactional problems. This paper describes a field study of remote interaction around objects that is telephone-centred, namely in a call centre for troubleshooting office devices. We describe how breakdowns in mutual orientation stem from three main problematics: 1) The inadequate fidelity of operators’ support resources; 2) The lack of mutual access to indicative resources; 3) operators’ lack of direct access to customers’ actions and orientation. From this analysis, we have developed a design proposal for supporting such work. Rather than using video, we propose that utilising a linked problem representation would address these problems. To this end we describe our proposal for a bidirectional remote visualisation of the troubleshooting problem.